PENGGUNAAN BAHAN AJAR BERORIENTASI PEMECAHAN MASALAH TERHADAP PENCAPAIAN HIGHER ORDER THINKING SKILLS (HOTS) SISWA DALAM PEMBELAJARAN FISIKA DI KELAS X - Fitri Nisak; Gusnedi Gusnedi; Amali Putra (PILLAR OF PHYSICS EDUCATION, 2018)
In Physics learning, students' thinking ability is still low. This is felt when students are given problems to be solved, such as solving problems related to high-order thinking skills. This study aims to determine the effect of teaching materials oriented problem solving on the achievement of HOTS students class X SMA N 12 Padang. This research belongs to a kind of quasi experiment with Posttest Only Control Group Design research design. The population of this study is all students of grade X SMA N 12 Padang registered in the academic year 2017/2018. Sampling was conducted by using Cluster Random Sampling technique to get class X IPA 1 as experiment class and class X IPA 5 as control class. The data collected are two primary and secondary data. Primary data in the form of data result of teaching materials and final test data. Secondary data is documentation data obtained through Physics teacher and administration. The data obtained were processed using t test and correlation test. after fulfilling normality, homogeneity and linearity. Furthermore the correlation test can be performed after the data is normally distributed and satisfies the linear relationship. According to the results of data analysis found the results as follows. There is an effect of 51% of problem-oriented teaching materials to solving HOTS students. Thus the working hypothesis which reads "there is a meaningful influence of the problem solve oriented learning material toward the achievement of Higher Order Thinking Skills (HOTS) in Physics learning in grade X SMA N 12 Padang" is acceptable.